Analisa Konstruksi Pada Modifikasi Penambahan Panjang BackhoeDeck LCB.Brahma Galaxy - Sandy Amrullah; Budianto Budianto; Rizal Indrawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
The barge backhoe deck is planned to be modified to add length so that analysis is neededregarding the strength of the structure, considering that most coal loading and unloading processestake place on the backhoe deck, so the safety of the backhoe deck structure is very important. In thisstudy, we will find out how much stress occurs on the backhoe deck by using the Finite ElementMethod as the media of analysis.From the results of the simulation and analysis it is known that themaximum voltage that occurs when the backhoe is not operating is equal to 24 MPa, and when thebackhoe is operating that is equal to 27.43 MPa. The maximum deflection when the backhoe is notoperating is 60.99 mm, and when the backhoe is operating that is 68.6 mm. Factor of safety when thebackhoe is not operating is 9.6 and when the backhoe is operating is 8.5.Based on the simulation themaximum voltage value is still below the permit voltage in the manual calculation, namely 166 Mpa.The deflection value of the simulation results is also still below the maximum deflection value that ispermitted in the manual calculation of 70 mm. The factor of safety value according to BKI can beconcluded that the construction of the backhoe deck is declared safe in loading when the backhoe isnot operating or when the backhoe is operating because it meets the safety factor requirements thatthe safety factor value must be more than 1.